Resolve the Clear‐Sky Continuous Diurnal Cycle of High‐Resolution ECOSTRESS Evapotranspiration and Land Surface Temperature. Issue 9 (16th September 2022) - Wen, Jiaming; Fisher, Joshua B.; Parazoo, Nicholas C.; Hu, Leiqiu; Litvak, Marcy E.; Sun, Ying
Abstract: Although numerous evapotranspiration (ET) estimates have been developed from remote sensing measurements, a diurnally resolved product with high spatial resolution (<100 m) is still lacking, which is critically needed for agricultural and ecological monitoring. The ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) provides, for the first time, ET at 70 m resolution with diurnal samplings, enabling a step toward filling this data gap. This study developed the first framework to resolve the full diurnal cycle of ET and Land Surface Temperature (LST) from sporadic ECOSTRESS measurements. We first constructed 70 m diurnal LST utilizing a diurnal temperature cycle (DTC) model that fused ECOSTRESS and Geostationary Operational Environmental Satellite (GOES) LST. Next, we derived 70 m diurnal ET from the diurnally resolved LST, along with ancillary meteorological and reflectance data sets, using the Priestley‐Taylor Jet Propulsion Laboratory (PT‐JPL) algorithm. This framework was tested in two regions: A relatively homogeneous semiarid grassland landscape (centered at the US‐Seg Ameriflux site) and a heterogeneous humid cropland landscape (centered at US‐ARM). Our diurnally resolved LST and ET successfully reproduced the spatial patterns in the native ECOSTRESS measurements during overpasses for both landscapes (LST: r  > 0.97, RMSE ∼2°C; ET: r  > 0.99, and RMSE = 1–7 W m −2 ). The constructed time series also well captured the temporal variability of the in situ measurements (especially under clear‐sky conditions) at both US‐Seg and US‐ARM, albeit performance varying with availability and quality of ECOSTRESS samples. This study sets the stage for testing and applying our framework to broader climates, biomes, and landscapes toward eventually generating diurnally resolved 70 m global operational LST/ET products to enhance ecological/agricultural applications. Key Points: We developed a framework to construct the clear‐sky diurnal cycle of ECOSTRESS land surface temperature (LST) and evapotranspiration (ET) The diurnally resolved 70 m LST/ET successfully reproduced the fine spatial variation in the native ECOSTRESS measurements The diurnally resolved LST/ET well captured the diurnal variation of independent in situ measurements, especially on clear‐sky conditions